Modifying the AES Algorithm by Improving the Add Round Key Stage - Hasan Kadhim A. Alsuwaiedi; Abdul Monem S. Rahma (Wasit Journal of Computer and Mathematics Science, 2023)
This study offers a new adjustment to the Advanced Encryption Standard (AES) in order to assure a high degree of security. This is achieved by replacing the binary (XOR) operation with a new (Xo) operation in each add-round-key stage. The Xo operation generated an extra six randomly selected control keys determined by six state tables (2, 4, 6, 8, 10, and 12) produced from the addition operation in the Galois Field GF (2^2 ,2^4 ,2^6 , 2^8, 2^10 and 2^12 ) in order to boost the algorithm's unpredictability. In the suggested method, an adversary requires at least  probabilities of keys to break the message; hence, it improves the difficulty of the original AES against brute force attacks. also enhances the performance of additional security metrics, such as NIST tests, compared to the original AES. Consequently, this replacement, including the use of six keys in both the encryption and decryption processes, offers a new level of security and a higher degree of resistance to data breaches. The novelty of the proposed (Xo) technique lies in the construction of GF tables ( 2^6 , 2^10 and 2^12) to be used in the encryption and decryption process for the first time, as well as the approach utilized to create the code for it.